Faktor Yang Berpengaruh Terhadap Kejadian Low Back Pain Pada Guru Di SMPN 1 Bathin Solapan - Yose Rizal; Futhri Rifa Zaimsyah (LPPM Universitas Abdurrab, 2021)
Low back pain is a major health problem in the workforce. Teachers are among the professions that are at high risk of suffering from low back pain due to work as social transformation, educational reforms and new teaching models have affected current teaching conditions, leading to changes in the profession in order to that teachers move from a relatively safe status to a state of instability in the workplace, due to new precarious and unregulated working methods. The aim of this study was to determine which risk factors are the causes of the low back pain (low back pain) experienced by the teachers of the SMPN 1 Bathin Solapan. This research uses quantitative methods. The research sample consisted of 28 teachers from SMPN 1 Bathin Solapan. The results of the analysis showed that there was no interaction variable (p <0.05) on the variables of age, sex, exercise routine and duration of sitting. From the results of this study, more research is needed to determine what other factors are associated with the incidence of low back pain in teachers at SMPN 1 Bathin Solapan.